Proceedings of the Ocean Drilling Program 1992
DOI: 10.2973/odp.proc.sr.127128-1.168.1992
|View full text |Cite
|
Sign up to set email alerts
|

Depositional and Diagenetic Behavior of Barium in the Japan Sea

Abstract: The barium distribution in sediments and pore fluids from five sites drilled in the Japan Sea have been used to illustrate the geochemical behavior of this element as it pertains paleoproductivity reconstructions, diagenetic remobilization, and barite precipitation in authigenic fronts. Sites where sulfate is depleted in the pore fluids also show high concentrations of dissolved barium, reflecting dissolution of biogenic barite. The high rate of sedimentation at Sites 798 and 799 results in a rapid sulfate dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…It is known that the formation of barites in marine basins was defined by two processes [20,[41][42][43]45 etc.]. The first process was the focused discharge of Ba bearing fluid immediately on the seafloor, which interacted with sulfate ions of seawater to produce openwork barite chimneys consisting mainly of barite with characteristic crystal morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the formation of barites in marine basins was defined by two processes [20,[41][42][43]45 etc.]. The first process was the focused discharge of Ba bearing fluid immediately on the seafloor, which interacted with sulfate ions of seawater to produce openwork barite chimneys consisting mainly of barite with characteristic crystal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Much less common cold gas-fluid flows bear, in addition to methane, other chemical components, in particular, barium, which results in the formation of not only carbonate but also barite mineralization in the sedimentary succession and on the seafloor [9,14,15,20,22,23,31,35,[38][39][40][41][42][43][44][45]. The largest known manifestations have been found and studied in detail in the Deryugin Basin in the Sea of Okhotsk [1, 5, 6, 8, 11, 16-18, 25, etc.].…”
Section: Introductionmentioning
confidence: 99%
“…Authigenic barite reprecipitation at the SMTZ most likely acts as a sink for dissolved barium (von Breymann et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Barite dissolution under anoxic conditions and consequent upward Ba diffusion into sulphate-bearing pore water lead to precipitation of authigenic barite in a diagenetic front. Thus, the barite front mainly marks the boundary between sulphate-rich and sulphate-poor pore waters (Cronan, 1974;Dean and Schreiber, 1978;von Breymann et al, 1992;Torres et al, 1996;Paytan et al, 2004;Hendy, 2010) that in the investigated AND-1B core portion can be identified with the Ba peak at the top of the diatomite sequence (at~363 mbsf). Strangely, other Ba peaks within the diatomite sequence are relative to samples in which the presence of pyrite and Fe-dolomite is documented (Fig.…”
Section: Element Geochemistrymentioning
confidence: 99%
“…The link between enhanced surface productivity and increased amount of barium in the sediment is thought to be associated with decay of phytoplankton Global and Planetary Change 102 (2013) [20][21][22][23][24][25][26][27][28][29][30][31][32] and inorganic precipitation of barite in water column or in supersaturated microenvironments at the seafloor (Dehairs et al, 1980;Bishop, 1988;Dehairs et al, 1991;von Breymann et al, 1992;Gingele and Dahmke, 1994;Paytan et al, 1996;Gingele et al, 1999;Ganeshram et al, 2003). On the other hand, under conditions of sulphate depletion in pore waters, which is usually encountered below oxygen-depleted bottom waters, the barite is dissolved and barium is released into the pore water (Brumsack and Gieskes, 1983;von Breymann et al, 1992;Gingele et al, 1999;McManus et al, 1999;Castellini et al, 2006;Scopelliti et al, 2006;Hendy, 2010;Henkel et al, 2012). In these conditions, increase of pH and carbonate alkalinity encourages the formation of dolomite and other authigenic carbonate (Vasconcelos and McKenzie, 1997;Warthmann et al, 2000;van Lith et al, 2003;Raiswell and Fisher, 2004;Scopelliti et al, 2009).…”
Section: Introductionmentioning
confidence: 99%